Finance and Development, December 2017. (Finance and Development; Finance and Development, 2017)
This paper analyzes that although demands for political transformation commanded the world's attention, those calls were largely motivated by unresolved socioeconomic issues. Demonstrators in the streets of Cairo and Tunis demanding bread, dignity, and social justice expressed widely held aspirations for basic economic rights, along with greater prosperity and equity. Almost seven years later, notable progress has been achieved in terms of public finance reforms. However, these reforms still have a long way to go to reduce disparities in the distribution of wealth within most countries of the region or narrow the development gaps between them. Countries in the Middle East and North Africa now face a stark choice between short-term retrenchment and resolute pursuit of the long-term reforms needed to secure their future economic prosperity. Forsaking important economic adjustments needed to strengthen inclusive growth and modernize the state and private sectors would set the region back, possibly for decades.